Protection of Grouper Against Cryptocaryon irritans by Immunization With Tetrahymena thermophila and Protective Cross-Reactive Antigen Identification - Mo, Zequan; Wu, Huicheng; Hu, Yingtong; Lai, Xueli; Guo, Wenjie; Duan, Yafei; Dan, Xueming; Li, Yanwei (Frontiers in Immunology, 2022)
Vaccination is an effective method to prevent Cryptocaryon irritans infection. Although some vaccines have been developed, large-scale production of these vaccines is costly. Development of a heterogenous vaccine generated by low-cost antigens is an alternative method. In the present study, grouper immunized with Tetrahymena thermophila, a free-living ciliate that easily grows in inexpensive culture media at high density, showed protective immunity against C. irritans infection. Higher immobilization against C. irritans theronts was detected in T. thermophila-immunized grouper serum, which suggested the existence of a cross-reactive antibody in the serum. By immunoprecipitation and mass spectrometry analyses, tubulin was identified as a potential cross-reactive antigen between C. irritans and T. thermophila. Recombinant T. thermophila tubulin protein (rTt-tubulin) and its antibody were prepared, and immunofluorescence showed that both C. irritans and T. thermophila cilia were stained by the anti-rTt-tubulin antibody. Grouper immunized with rTt-tubulin showed a reduced infective rate after the C. irritans challenge. An enhanced level of C. irritans-binding IgM antibody was detected in serum from rTt-tubulin-immunized grouper. Moreover, specific antibodies were also found in the mucus and tissue culture medium from rTt-tubulin immunized grouper. Overall, these findings suggested that vaccination with T. thermophila elicits cross-reactive protective immunity in grouper against C. irritans, and T. thermophila may be a potential heterologous antigen for vaccine development.